Variabilidade entre isolados de Cowpea severe mosaic virus por meio de caracterização biológica, sorológica e molecular - Silva, Ana Kelly Firmino da (2017)
Cowpea (Vigna unguiculata subsp. unguiculata) is grown as staple food for the rural and urban populations inf the North and Northeast Brazil. It has great importance as a generator and income, being cultivated by small to medium producers. Brazil is the largest producer of beans [ commob bean (Phaseolus vulgaris) and cowpea] with production of 2.5 milion tons in the 2015/16 harvest, being the States of Paraná and Minas Gerais the largest producers of common bean, and State of Ceará in ninth position. Several factors affect the cowpea crop influencing the quality and quantity produced, highlighting the viruses as responsible for large losses in the crop. Several species of virus can naturally infect cowpea, especially the Cowpea severe mosaic virus (CPSMV). The objective of this research was to study the genetic variability among eight isolates of CPSMV obtained in different States of the Northeast region, through biological, serological and molecular characterization studies. The experiments were carried out in a greenhouse and in the Plant Virology Laboratory of the Federal University of Ceará. The CPSMV-MC isolate was purified from cowpea cv. Macaibo, obtaining a virus preparation with a concentration of 64.83 mg of virus per kg of infected tissue and antiserum title of 1: 1024 in Double Immune Diffusion Test. The biological study, by partial range of host plants showed symptomatological difference between the CPSMV-MC isolate of the others. The results of the serological study showed that the CPSMV-MC isolate may be serologically distinct when using antiserum produced from this isolate. The electrophoretic analyzes revealed two bands related to the weight of the capsidial protein formed by 22.5 kDa and 39 kDa structural proteins. Comparison between variations in the PTA-ELISA technique, showed that IP-PTA-ELISA, was efficient and reliable for detection of CPSMV suppressing the problems of virus of the genus Comovirus that do not adhere adequately to the Of ELISA plates. In the molecular study, the primers designed for the partial genome of RNA1 and RNA2 regions could be used for both detection and sequencing of the virus. The phylogenetic analyzes of the sequences of the CPSMV isolates, using primers for the RNA1 region revealed a difference between the CPSMV-MC isolate and the others, making it possible to fit them into two groups. One group that causes severe symptoms, adding seven isolates of CPSMV and the other group with only one isolate that causes mild symptom (CPSMV-MC) in cowpea. The study of the interaction between the virus that infects cowpea 'Setentão' showed strong synergism between CPSMV, Cowpea aphid-borne mosaic virus (CABMV) and Cucumber mosaic virus (CMV), leading in some cases to death of the plant, mainly when interacting Of these three viruses, and two of these isolates showed severe symptoms in the plants when in simple infection. Studies of this nature involving aspects related to pathogens and the plant produce important information in the research programs that aim at the selection and production of virus resistant cultivars.